Spatial mapping of metals in tissue-sections using combination of mass-spectrometry and histology through image registration - Anyz, Jiri; Vyslouzilova, Lenka; Vaculovic, Tomas; Tvrdonova, Michaela; Kanicky, Viktor; Haase, Hajo; Horak, Vratislav; Stepankova, Olga; Heger, Zbynek; Adam, Vojtech (Scientific reports, 2017)
We describe a new procedure for the parallel mapping of selected metals in histologically characterized tissue samples. Mapping is achieved via image registration of digital data obtained from two neighbouring cryosections by scanning the first as a histological sample and subjecting the second to laser ablation inductively coupled plasma mass spectrometry. This computer supported procedure enables determination of the distribution and content of metals of interest directly in the chosen histological zones and represents a substantial improvement over the standard approach, which determines these values in tissue homogenates or whole tissue sections. The potential of the described procedure was demonstrated in a pilot study that analysed Zn and Cu levels in successive development stages of pig melanoma tissue using MeLiM (Melanoma-bearing-Libechov-Minipig) model. We anticipate that the procedure could be useful for a complex understanding of the role that the spatial distribution of metals plays within tissues affected by pathological states including cancer.
Keywords: melanom; Copper; histologické techniky; modely nemocí na zvířatech; Histological Techniques; Zinc; zvířata; zinek; počítačové zpracování obrazu; Image Processing, Computer-Assisted; pilotní projekty; Pilot Projects; Swine; měď; Melanoma; Animals; Disease Models, Animal; hmotnostní spektrometrie; prasata; Mass Spectrometry